THE DZUNGARIAN ASPECT OF KYRGYZ HISTORY IN THE RESEARCH OF ACADEMICIAN ABYLABEK ASANKANOV (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
A deep and thorough study of the history of Kyrgyzstan directly depends on the personal initiatives and efforts of individual historians. In this article, we tried to dwell in detail on the specifics and conclusions of the research of a scientist who studied «centaurs» (Kyrgyz riders) on the Eurasian continent, especially in Rongguo. As a scientific source, the works of the scientist and scientific, documentary, genealogical materials published in China were used
Keywords: history, Jungo, Abylabek Asankanov, research